Newly Recorded Lepista sordida (Schumach.) Singer (Agaricales Tricholomataceae) for Indonesia - Atik Retnowati (Floribunda, 2019)
Lepista sordida (Schumach.) Singer is firstly reported from Indonesia. Description and illustration of the species are presented.